ENERGY RELATIONS BETWEEN RUSSIA AND UKRAINE AFTER THE EUROMAIDAN: TRAPPED BETWEEN THE CONTRACTUAL SPACE AND THE SPACE OF SPACES - Eric PARDO SAUVAGEOT (Challenges of the Knowledge Society, 2016)
Russia-Ukraine energy relations have been mired in constant tension and contract renegotiations since the fall of the Soviet Union. Major examples of the conflict ridden character of mutual energy relations are the big disputes of January 2006 and January 2009 which translated into grave disruptions of energy flows to other European countries further west. The new period opening with the contract signed in January 2009 and later with Viktor Yanukovich´s presidency seemed to have ushered Ukraine and Russia into a period of relative stability. That situation floundered with the onset of the Euromaidan, the ousting of Ukraine´s President Viktor Yanukovich and the arrival in Kiev of new authorities which Moscow perceived as hostile. Energy relations were necessarily affected by a new context where both countries entered a period of armed confrontation. In this presentation, I will analyze energy relations between Russia and Ukraine since the Euromaidan using as analytical tools the characterization made by Katja Yafimava of four different spaces to understand how energy relations unfold in the post-Soviet space: regulatory space, space of flows, contractual space and space of places. This seems particularly warranted as in our case we find that particular changes (or lack thereof) in both the contractual space and the space of spaces determined to which degree energy relations between our two countries moved towards a pattern of conflict. This way, we may extract valuable lessons as for the way mutual relations are constructed and either politicized or de-politicized depending on the circumstances. This may provide a guide to consider how energy relations may evolve in the coming future, especially if diplomatic relations stay in their current stage since Russia decided to annex the Peninsula of Crimea and support separatist militias in the Donbass region.